HTRA1/lncRNA HTRA1-AS1 dominates in age-related macular degeneration reticular pseudodrusen genetic risk with no complement involvement - Farashi, Samaneh; Abbott, Carla J.; Ansell, Brendan R. E.; Wu, Zhichao; Altay, Lebriz; Arnon, Ella; Arnould, Louis; Bagdasarova, Yelena; Balaskas, Konstantinos; Chen, Fred K.; Chew, Emily; Chowers, Itay; et al. (Nature Communications, 2025)
Age-related macular degeneration (AMD) is a multifactorial retinal disease with a large genetic risk contribution. Reticular pseudodrusen (RPD) is a sub-phenotype of AMD with a high risk of progression to late vision threatening AMD. In a genome-wide association study of 2165 AMD+/RPD+ and 4181 AMD+/RPD- compared to 7639 control participants, both chromosomes 1 (CFH) and 10 (ARMS2/HTRA1) major AMD risk loci are reidentified. However association is only detected for the chromosome 10 locus when comparing AMD+/RPD+ to AMD+/RPD- cases. The chromosome 1 locus is notably absent. The chromosome 10 RPD risk region contains a long non-coding RNA HTRA1-AS1 (ENSG00000285955/BX842242.1) which colocalizes with genetic markers of retinal thickness. HTRA1-AS1 has a strong retinal eQTL signal, pinpointing the parafoveal photoreceptor outer segment layer. Whole genome sequencing of phenotypically extreme RPD cases identifies even stronger enrichment for the chromosome 10 risk genotype.
Online veröffentlicht: 08. Dezember 2025
Gesehen am 20.02.2026